Relevance of the adrenocortical hormone aldosterone to long-distance swimming - Skipka, W. (Swimming Science V, 1988)
Earlier investigations have demonstrated that injection of the mineralocorticoid hormone aldosterone increases the oxygen uptake during submaximal and maximal exercise on a cycle ergometer (Skipka & Schoning, 1981). Experiments by Bedrak and Samoiloff (1%7) demonstrating a higher activity of muscular oxidative enzymes after aldosterone injection and by Wong and Walsh (1971), who observed an increased oxygen uptake of rat diaphrams caused by aldosterone, indicate that the augmented oxygen uptake after aldosterone application is due to an augmented aerobic metabolic rate of muscles. The present study was designed to investigate whether the aldosterone-induced increase of the arobic metabolism leads to an improvement of performance capacity of long-distance swimmers.